Faktor-Faktor yang Berhubungan dengan Persalinan Preterm di RSU Santo Vincentius Kota singkawang - Umi Fania Julianti (KUNKUN: Journal of Multidisciplinary Research, 2024)
Preterm labor often occurs in pregnancy, this is shown in cases that occurred in 2018, around 25.2% of mothers who gave birth experienced premature labor, which is the main cause of 60-80% of neonatal morbidity and mortality in the world, while in Indonesia the incidence of premature labor is around 19 % of the number of neonates. The research design is analytical observational research. The case control research design used a retrospective approach. This research was conducted in September 2019. The research was carried out in the Midwifery Room at RSU St. Vincentius Singkawang The research population was all mothers in labor who were cared for in the obstetrics room at RSU St. Vincentius Singkawang in 2020, namely 524. The case sample in this study was mothers giving birth with premature parturition, while the control sample was mothers giving birth with term parturition. So the case samples were 37 samples, while the control samples were 37 samples with a ratio of 1:1. So the total sample in this study was 74 mothers giving birth. The sampling technique for cases used a total sampling technique, namely all 37 mothers who experienced premature labor. Meanwhile for controls used a random sampling technique, namely systematic sampling. The variables consist of the dependent variable, namely preterm birth, while the independent variables are age, parity, history of PROM. The data collection method uses secondary data collected from written reports in the medical records of RSU St. Vincentius Singkawang. The data collection instrument used in this research was a checklist sheet. The data analysis used was Univariate and Bivariate using Chi Square. The results of the study showed that there was no relationship between maternal age and premature birth with a p value of 0.277, there was a relationship between parity and premature birth with a p value of 0.000. There is no relationship between history of PROM and premature labor with a p value of 1,000